MODEL PEMBELAJARAN PERMAINAN TENIS LAPANGAN BAGI MAHASISWA - Sukadiyanto Sukadiyanto (Universitas Negeri Yogyakarta, 2005)
Abstract This research was aimed at finding out the effectiveness of a groundstroke skill instructional model for the beginner tennis players among the 8 university students. The population was the students of the 2001 and 2002 academic years of the Department of Sport Trainer Education, Faculty of Sport Science, of the State University of Yogyakarta,who took the Lawn Tennis as one of their compulsory courses. The sample was 26 students chosen randomly from the total of 48 students of the 2001 academic years students and 22 students chosen randomly from the total of 39 students of the 2002 academic year students. The students of the 2001 academic year took the course conducted by the open instructional model, while the students of the 2002 academic year took the course conducted by the closed instructional model. The results of the analysis indicates that: (1) there is no differences in groundstroke skills between the tennis players learn by open model and those learn by the closed model, (2) the tennis players with high coordination capability perform better groundstroke skills than those with the lower coordination capability, and (3) there is no interaction between instructional model and coordination capability with respect to their effect on the students groundstroke skills. Keywords: instructional model, lawn tennis.